2008
DOI: 10.1902/jop.2008.080033
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine Intake Increases the Risk for Periodontal Destruction in Subjects With Type 2 Diabetes Mellitus

Abstract: NIF intake may increase the risk for periodontal destruction in patients with type 2 DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…These results confirm the association of inflammatory gingival enlargement with drug induced overgrowth. These results are in accordance with the recent epidemiologic study by Li et al, in 2008 which showed the increase in attachment loss and bone loss in patients taking nifedipine as an antihypertensive. [19][20][21] Histopathological examination revealed the mixture of dense and loose fibrous components with chronic inflammatory cell infiltrate in the connective tissue.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirm the association of inflammatory gingival enlargement with drug induced overgrowth. These results are in accordance with the recent epidemiologic study by Li et al, in 2008 which showed the increase in attachment loss and bone loss in patients taking nifedipine as an antihypertensive. [19][20][21] Histopathological examination revealed the mixture of dense and loose fibrous components with chronic inflammatory cell infiltrate in the connective tissue.…”
Section: Discussionsupporting
confidence: 92%
“…Generalized gingival enlargement was reported and the combination of inflammatory and drug induced overgrowth is more pronounced in mandibular anterior region due to the more plaque accumulation. [22,23] Periodontal pocket depths from 3 to 8 mm were recorded with greater depths up to 8 mm in relation to mandibular anteriors. Grade III mobility was recorded in relation to mandibular anteriors which were extracted during the maintenance phase according to the patients' acceptance.…”
Section: Discussionmentioning
confidence: 97%
“…Although we could not check the type of medication used by the subjects being treated for hypertension, the calcium ion channel blocker nifedipine is reported to be associated with gingival hyperplasia 19 . One study 20 showed nifedipine intake increased the risk of periodontal destruction in subjects with type 2 diabetes mellitus. These studies provide evidence to explain the relationship between hypertension and periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that hypertension was associated with greater tooth loss. The control of hypertension in diabetics and its inter‐relationship with periodontal destruction was also studied in Chinese diabetic and hypertensive subjects in China medicated with nifedipine, a calcium channel blocker, and it was suggested that nifedipine increases the risk for periodontal destruction in diabetics (88). In gutka chewers with diabetes, the deleterious effect of gutka on periodontal disease was masked by the deleterious effects of diabetes (70).…”
Section: Microbiological Associations With Periodontal Diseasementioning
confidence: 99%